Sintesis Biopelumas Dari Minyak Biji Karet: Pengaruh Katalis NaOCH3 Dan Waktu Reaksi Terhadap Yield Biopelumas - Yursal, Muhammad Habibie; Irdoni, Irdoni; Nirwana, Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Lubricants are used in machines to reduce friction between two metal objects so that they can overcome wear on engine components. Rubber seed oil is a type of non-food oil (oil that cannot be consumed) because there is a cyanide compound (HCN) so that it can be used as raw material for making biolubricant. This research aims to synthesize biolubricant based rubber seed oil and study the effect of the percentage of addition of NaOCH3 catalysts and reaction time to yield of biolubricant produced. This research was carried out in several stages: preparation of raw materials including extraction of rubber seed oil by pressing method, then continued by degumming process to purify the oil from the gum. Next, the esterification process to reduce of free fatty acid at the oil. The final stage is the transesterification process of making biolubricant with a mole ratio of oil and 1-octanol of 1:5, reaction temperature of 170 oC, stirring speed of 200 rpm, time variation for 4 hours; 6 hours; 8 hours, and variations in the number of catalysts are 2%; 3%; 4% v/v oil. The highest yield of biolubricant produced was 82.635%. The best characteristics of biolubricant were produced at 4 hours reaction time and 4% catalyst with density values of 0.8344 gr/ml, viscosity index 217.568, pour point -9 oC, flash point 295 oC, and FTIR test to ensure the formation of ester functional groups in biolubricant.Keywords: Biolubricant, rubber seed oil, octanol, transesterification